Pemberdayaan Kelompok Pemuda Putus Sekolah Melalui Pengolahan Limbah Pertanian Menjadi Ransum Organik di Desa Cakkela Kabupaten Bone - Mahfud, Andi Muhammad; Asfar, Andi Muhammad Irfan Taufan; Safar, Muhammad; Asfar, Andi Muhamad Iqbal Akbar; Nurannisa, Andi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to empower out-of-school youth groups by processing agricultural waste into nutritious organic rations. The method of implementing this activity was carried out using the society participatory method which fully involves partners during the activity with several steps including the tudang-sipulung (extension), assama'turu (training), and sipakatau (mentoring) stages. To measure the increase in knowledge and skills of partners during the implementation of the program, pretest and posttest instruments were used in the form of a Google form, then analyzed using quantitative descriptive in the form of a gain score (N-Gain). The results of the community service indicated that the knowledge and skills of partners increased with four assessment components, namely knowledge of waste processing increased by 80%, waste processing skills (production) increased by 90%, marketing skills, and financial management each by 80%. The increased skills of partners have the potential to open up business opportunities with added value in the processing of agricultural waste ranging from rice husks, corn cobs, and peanut skins as useful and economical products so that they can be a support in meeting independent alternative feed by the Cakkela Village government.